Hasil pendaftaran perusahaan/usaha (angka tetap) (Sensus ekonomi 1986., 1987)
Results of the 1986 economic census on corporate enterprises and home-based businesses in Kabupaten Jeneponto, Propinsi Sulawesi Selatan.